A NOVEL TABLE TENNIS ROBOT USING ARDUINO - M.Pradeep, Ayyappa Srinivasan M G (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
In this work, a Smart Ping Pong Robot has been suggested. This robot is being used exclusively for table tennis applications so that the player can practise or play without an opponent. The ball is automatically thrown by the robot so that players can compete against it. In this system, the actuator, also known as the crank shaft piston, is powered by a power source. 12 volts DC are created by converting the power source (230V AC). The crank shaft piston moves mechanically as a result of the electrical energy.The ball is fed from the basket to the end effector using this piston (Ball delivery). When a DC wiper motor is activated, a DC wiper motor is fixed at the bottom of the disc, and the disc is turned 45 degrees to the left and 45 degrees to the right. in order for the ball to be delivered in the forehand and middle forehand directions. Moreover, the ball is given top, side, and reverse spin by this robot.Thge design of the work has one degree of flexibility, and it rotates to deliver balls in various directions. Thus, our robot plays a positive role in the robot table tennis development.